EXPLANATION Of KAWASHI For IMAM MUWAFFAQ Al-DIN AHMAD IBN YUSUF Al-KAWASHI (680 AH) STUDY and REALIZATION Of SSURAH Al-HAMZA - Ali , Saadi; Hussein, Raheem (Islamic Sciences Journal, 2023)
Explanation of Al-Kawashi for Imam Muwaffaq al-Din Ahmad ibn Yusuf al-Kawashi (680 AH) Study and realization of Al-Hamza The Explanation of Al-Kawashi is one of the important Explanations that contained the language, significance, meanings, readings, rulings and opinions of the scholars who preceded him. Al-Hamza is one of the mysteries of this interpretation. It deals with the eloquent meanings and the beautiful language of the vocabulary mentioned in this surah, and then explains it clearly. The reader does not find it difficult to understand and know the meaning of God from the verses. The readability corresponds to the reading, as well as the facets